Juliane Noth, Transmedial Landscapes and Modern Chinese Painting. Harvard University Press, 2022. 400 pp. - Próspero Carbonell (Hart)
Reseña. Juliane Noth, Transmedial Landscapes and Modern Chinese Painting. Harvard University Press, 2022. 400 pp.